Kapasitas Keuangan dan Kesadaran Atas Produk Keuangan:Survei Rumah Tangga Berpenghasilan Rendah di Jabodetabek dan Surakarta, Indonesia - Danarsari, Dwi Nastiti; Viverita, Viverita; Husodo, Zaäfri A. (Jurnal Manajemen dan Usahawan Indonesia, 2021)
This study aims to examine the relationship between financial capacity and awareness on financial product for low-income households in Jabodetabek and Surakarta by conducting survey on 1,520 household respondents. The survey results show that saving account and credit for vehicle owner- ship are the two most popular financial products known by the respondents. In addition, the cross- tabulation and chi-square analysis find that Jabodetabek’s respondents, who ever have and are using financial product, mostly have stronger financial capacity. On the other hand, respondents who never have and are not using financial product are those who have weaker financial condition. Moreover, respondents in both regions, who never own and are not having credit for vehicle ownership, mostly have relatively weaker financial capacity. The results indicate that financial capacity is associated with awareness on financial product.